Exploring the Students’ Mathematical Communication Ability Related to Learning Style Appertaining to Junior High School - Ramadoni, Ramadoni; Chien, Kao Tai; Oktamira, Doli (Journal of Instructional Mathematics, 2024)
The scarcity of mathematical communication abilities needed attention along with students' learning styles as a personal characteristic causing these abilities to differ. This descriptive study aimed to determine the mathematical communication abilities of students with specific learning styles. Eighth-grade public junior high school students (N=23) in Lembah Gumanti participated in this study to complete a learning style questionnaire and a mathematical communication abilities test. The study found that the visual learning style was most dominant, with the highest percentages in the high and low ability categories, and equal to auditory in the medium category but lower than kinesthetic. Students with a kinesthetic learning style in the low and high ability categories both had the same percentage as students with an auditory. There were strong mathematical communication abilities in the dual learning style of auditory-kinesthetic. Auditory students, regardless of their ability levels, made errors in mathematical symbols, so their communication abilities varied based on understanding and symbol usage. Visual and kinesthetic learners generally excelled in articulating and solving problems. Based on these results, it is recommended that teachers consider students' learning styles to be able to use appropriate models to improve students' mathematical communication abilities.